Analysis of the Distribution of White Spot Syndrome Virus (WSSV) in Vannamei Shrimp (Litopenaeus vannamei) in Bali: Water Quality and PCR Study - Billy Andri Agrifa Barus; Gede Iwan Setiabudi; Hamdanul Fain (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
White Spot Syndrome Virus (WSSV) is a pathogen responsible for white spots, typically 0.5–2 mm in diameter, on the shrimp cephalothorax. WSSV is capable of causing mass mortality rates of up to 100% within 3 to 10 days of symptom onset. The rapid transmission and detection challenges associated with WSSV have resulted in significant economic losses for Indonesian shrimp farmers. In Bali, Litopenaeus vannamei (Vannamei shrimp) is the second-largest marine aquaculture commodity after seaweed, with major seed production centered in the Gerokgak and Seririt Districts of Buleleng Regency. Given the difficulty in controlling WSSV, identifying its emergence and characteristics is critical. This study aimed to determine the distribution of WSSV in Bali by examining the relationship between water quality and Polymerase Chain Reaction (PCR) detection results, and by analyzing the correlation between water quality, WSSV incidence, and mortality rates in monitoring ponds. The research focused on PCR analysis and water quality assessment of Vannamei shrimp from the Karangasem, Buleleng, and Jembrana Regencies, conducted by the Indonesian Quarantine Agency (BKI). Water quality parameters, including temperature, transparency, pH, DO, salinity, nitrite, nitrate, ammonia, and phosphate, were measured using test kits. The study detected no WSSV during the examination period. PCR analysis showed amplification products ranging from 200 to 400 bp, distinct from the standard WSSV-positive marker at 941 bp. Furthermore, all water quality samples met the criteria and compliance parameters established by the Animal, Fish, and Plant Quarantine Center (BBKKIT).